(untitled) (Research, Society and Development, 2020)
The present work aims to evaluate the Minimum Inhibitory Concentration of Adherence (MICA) of the essential oils of Eucalyptus globulus and Eucalyptus citriodora against the bacterium Klebsiella pneumoniae. It was performed the determination of the Minimum Inhibitory Concentration of Adherence (MICA) using the inclined tube technique, in the presence of 5% sucrose. After 24 hours, the reading was performed through visual observation of the bacterium’s adherence to the tube walls. It was observed that the essential oil of Eucalyptus globulus showed a good antiadherent efficiency to the strain of Klebsiella pneumoniae, showing biofilm inhibition at a concentration of 1:8 similar to the 0.12% chlorhexidine digluconate control. Eucalyptus citriodora oil did not inhibit biofilm formation in any of the tested concentrations. It was concluded that only the essential oil belonging to the Eucalyptus globulus species, showed antiadherent action against the strain of Klebsiella pneumoniae, which can be used as an alternative method to combat biofilms produced by K. pneumoniae.